Technical features and current trends of hip arthroplasty in patients with ankylosing spondylitis - I. V. Polevoy; A. A. Roskidaylo; A. M. Lila; M. A. Makarov (Современная ревматология)
Coxitis is one of the clinical manifestations of ankylosing spondylitis (AS). It is considered an unfavorable prognostic factor and plays a key role in patients' disability. As the disease progresses, total hip arthroplasty (THA) is indicated. It helps to improve functional status and quality of life, as confirmed by both short-term and long-term observations. However, there are still a number of issues related to THA that are being discussed: types of anesthesia care, choice of surgical access, positioning of acetabular component in ankylosis, the feasibility of tenotomy in unresolved hip contracture, the possibility of simultaneous surgery on both sides, the sequence of interventions in spinal ankylosis resolution in patients with AS. All these supports the need for further study of this problem.